Features of Rhythm in Omar Yahya's Poetry (Journal of Hama University, 2020)
This research explores the features of rhythm in Omar Yahya's  poetry, Hama's poet, for rhythm is more comprehensive than prosodic rhyme, and rhyme is part of it. It appears through the internal rhythm by the repetition and consistency of letters and words. It also appears through using diction related to the phonological dimension which creates a certain music to the audience. It is reflected, as well, through colour and its variations and through movement rhythm of images and actions. All these reflections of rhythm express the psychological rhythm of the poet himself. This rhythm and its various features and its rhythmic switching which was a turning point in the works of Omar Yahya who is known well as a classical poet, all these are considered by some critics and researchers as technical defects and shortcomings. These defects are represented in his non-commitment to one rhyme in the same poem, leaving lexical decoration, changing words according to the necessity of rhythm and using redundant words.  I shall focus in this research on Omar Yahya's poetry from a rhythmic point of view leaving focus on prosodic rhymes. So, I hope through this study to shed light on one characteristic of the different and various characteristics of his poetry, so that I might do him little justice, as a talented poet.